PHOTOGRAPHY, CURATION, CRITICISM : an anthology. - Wells, Liz, 1948- ([S.l.] : ROUTLEDGE, 2023)
This unique collection brings together the work of photography writer, curator, and lecturer, Liz Wells, reflecting on key themes of landscape, place, nationhood, and environmental concerns. A newly written introductory chapter contextualizes the collection. This is followed by an in conversation' with Martha Langford, Concordia University, Montreal, that brings together two leading figures in the field to respond to Wells' thought and the themes that emerge in her writings. The essays included in this anthology draw on work from a variety of sources including artists' photobooks, exhibition catalogues, magazines, academic books, and journals. Seventeen previously published articles, organized thematically in relation to Curation and Residency, Phenomena, Place, and Critical Reflections, demonstrate Wells' critical and curatorial approach to research through photographic practices, reflecting a core view of art (at its best) operating to convey the implications of what is being explored and to evoke responses that are simultaneously sensory and intellectual. This collection will be essential reading for students and scholars of photography, visual culture, and art history, especially those examining landscape and environmental photography.
Keywords: PHOTOGRAPHY / Criticism; ART / History / General; Photographic criticism